Comparative study of neoadjuvant chemoradiotherapy, chemotherapy, and chemoimmunotherapy for locally advanced esophageal squamous cell carcinoma - Liu, Likun; Liu, Junhong; Rong, Yu; Zhang, Shuai; Ding, Yan; Zhang, Weili; Wang, Lan; Liu, Junfeng; Zhu, Shuchai (BMC cancer, 2025)
This study aimed to compare the efficacies of neoadjuvant chemoradiotherapy (NCRT), chemotherapy (NCT), and chemoimmunotherapy (NCIT) in patients with locally advanced esophageal squamous cell carcinoma (LAESCC). The primary objective was to assess the overall survival (OS) among the three treatment groups. A retrospective cohort of 625 patients treated at the Fourth Hospital of Hebei Medical University between 2016 and 2022 was analyzed. Patients received NCRT, NCT, or NCIT followed by radical esophagectomy. To adjust for confounding factors, inverse probability of treatment weighting (IPTW) was employed. Chi-square tests, Fisher's exact tests, and multivariate Cox survival analyses were used to assess prognostic factors and survival outcomes. Before IPTW, significant differences in baseline characteristics were observed among the three groups. After IPTW adjustment, differences were mitigated, allowing for a balanced comparison. NCIT demonstrated superior 4-year OS rate (91.4%) compared with NCRT (60.4%) and NCT (62.5%). The addition of adjuvant therapy further improved survival outcomes. NCIT may offer superior survival benefits over NCRT and NCT in patients with LAESCC, particularly when combined with adjuvant chemoimmunotherapy (ACIT). These findings underscore the potential of immunotherapy in multimodal treatment of LAESCC and warrant further investigation in prospective clinical trials.